Tibial Plateau Fractures in Low- and Middle-Income Countries: A Systematic Review of Treatment Modalities, Functional Outcomes, and Complications - Gasoma, Elmuhtadibillah Babiker Yousif; Sarhan, Mohamed Ahmed; Aly, Moustafa Sameir Hussein (The Surgery Journal, 2025)
Tibial plateau fractures (TPFs) are complex intra-articular injuries associated with long-term disability if not optimally treated. In low- and middle-income countries (LMICs), where high-energy trauma is prevalent and health system resources are constrained, management strategies, and outcomes differ substantially from those reported in high-income countries. This systematic review synthesizes evidence from LMICs on treatment approaches, functional outcomes, and complications following TPFs.We systematically searched PubMed, EMBASE, Scopus, and regional databases for studies conducted in LMICs, published up to May 2025. Eligible studies included adult patients with TPFs managed surgically, reporting functional or radiological outcomes. Data were extracted on demographics, fracture type, surgical technique, and outcomes. Risk of bias was assessed using the Newcastle–Ottawa Scale and Cochrane ROB-2 tools.Fifteen studies comprising 1,213 patients from South Asia, and Africa were included. Patients were predominantly male (65–75%) with mean ages between 35 and 45 years; road traffic accidents were the leading cause. Dual plating yielded superior alignment and higher Knee Society Scores (75–85) but carried increased infection rates (10–18%). Ilizarov and hybrid fixators achieved high union rates (>90%) with acceptable function, although pin-tract infections (15–20%) and malalignment (10–12%) were common. Arthroscopic-assisted fixation improved articular reduction but was limited to tertiary centres. A randomized trial demonstrated that immediate weight-bearing enhanced gait recovery without increased implant failure. Across studies, complication rates exceeded those reported in high-income countries, reflecting systemic barriers such as limited rehabilitation access, implant scarcity, and inadequate soft tissue care.In LMICs, satisfactory union and functional recovery can be achieved following TPF surgery, but complication rates remain high. Dual plating offers superior stability, while Ilizarov fixation provides a resource-appropriate alternative. System-level improvements in rehabilitation, infection prevention, and trauma infrastructure are critical to narrowing outcome disparities with high-income countries.
Keywords: tibial plateau fracture; LMIC; external fixation; dual plating; Ilizarov; functional outcome